Experimentos em ondas e acústica para auxiliar o processo ensino e aprendizagem da física no ensino médio - Silva, Klaus Nogueira da (2012)
This paper describes the development of experimental activities with the aid of the microcomputer as a measuring tool in the laboratory teaching of physics, as well as an account of his experience in the classroom. Using the software Audacity activities were carried out involving acoustic wave phenomena and as an aid for the development of a significant learning in high school. As theoretical references were used sociointeractionist theories of Vygotsky and Ausubel's meaningful learning. The instructional material was applied to two groups of high school students: a State School Marechal Rondon - Guara / SP and other College Evolution - Guara / SP. The learning experience is described in this paper and the product was produced education tours for student experiments.